Factores que influyen en la implementación de un protocolo de buenas prácticas agrícolas en la producción de plátano – distrito de Indiana – Loreto – 2022 - Isla Reategui, Gonzalo Manuel (2023)
In the area of Mazán - Indiana, considered a producer of Musa paradisiaca, banana, this research was carried out, with the objective of determining the factors that influence the implementation of a protocol of good agricultural practices, in the indicated crop. It is a descriptive, transversal work. The sample was 30 banana producers living in the study area. The results reached were: socioeconomic factors reach 20% of compliance with the GAP, the property does not have hygienic services, rest areas, warehouses, basic services, infrastructure condition (regular). Sociocultural factors meet 42%. The level of education achieved stands out, such as primary (46.7%) and secondary (40%), they have lived in the area for more than 30 years, have banana productive areas (0.5 - 2 hectares), they keep domestic animals and are aware of receiving training in the subject. Since they do not receive training in GAP, they do not apply it, they do not receive technical assistance on the crop, nor do they keep records of their daily activities (expenses on products, application of fertilizers or pesticides, they do not perform crop rotation, or soil analysis. only 42% meet this variable. For legal factors: land tenure, private predominates. There is no association of producers, nor do they make improvements to their productive activity and they do not verify productive aspects that can optimize their harvests. Only 20 are met. %. The derivations of the work show that there is power of the economic, sociocultural and legal components that do not allow the execution of a protocol of Good Agricultural Practices in this area.